Digital Citizenship Framework: A Systematic Review of Contemporary Elements and Implementation Challenges - Muhammad Zia ul Haq; Sangkala, Ismail (FKIP Unismuh Makassar, 2025)
Digital citizenship has evolved from a simple concept of technology access to a comprehensive framework encompassing ethical, social, and environmental dimensions of digital participation. This systematic review examines contemporary digital citizenship frameworks and their implementation challenges globally and within the Indonesian context. To systematically analyze the evolution of digital citizenship concepts, identify key elements in contemporary frameworks, and assess implementation challenges across different contexts, with particular attention to the Indonesian landscape. A systematic review was conducted following PRISMA guidelines. Literature from 2008-2024 was searched across multiple databases including academic journals, policy documents, and institutional reports. The search focused on digital citizenship frameworks, implementation strategies, and cultural adaptations. The review identified twelve core elements of contemporary digital citizenship: digital access, digital communication, digital literacy, digital ethics, digital security, digital law, digital rights and responsibilities, digital health and wellness, digital commerce, digital sustainability, digital belief, and digital education. Key challenges include the digital divide, insufficient digital literacy, cultural adaptation needs, and regulatory gaps. The Indonesian context presents unique opportunities through local wisdom integration (gotong royong, musyawarah mufakat) while facing infrastructure and literacy challenges. Digital citizenship requires a holistic, culturally-sensitive approach that balances universal principles with local values. Future research should focus on measurement frameworks, long-term impact assessment, and culturally adaptive implementation strategies.